Creating the path to success: The impact of crowdsourced exploratory and exploitative activities of expert graphic designers on creativity performance. (May 2021) - Xu, Yu; Sun, Yao; Cruz, Ignacio; Fulk, Janet
Highlights: This study analyzed behavioral evolution in crowdsourcing competitions. An increase in design expertise led to a decrease in exploration. An increase in design expertise led to an increase in exploitation. Exploitation was positively related to average score rated by crowd members. Neither exploration nor exploitation predicted product selection. Abstract: This article investigates (a) how serial idea generators in crowdsourcing contests adjust strategies (e.g., exploiting existing expertise and exploring new approaches) over time in response to the relative success of their prior creative ideas, and (b) how these changes in competitive strategies influence subsequent creativity performance. The research was conducted on Threadless, a website that crowdsources the creation of graphic designs through an ongoing competition. Empirical results from a longitudinal sample of 86 serial designers and their 1, 714 submissions indicated that a higher level of design expertise was related to less exploration and greater exploitation behavior. Exploitation was also found to contribute to generating ideas that were highly rated by the crowd. For the crowdsourcer's decision as to whether to transform a submitted idea into a product for sale, neither exploration nor exploitation was found to be significant when controlling for crowd rating. Theoretical and practical implications for crowdsourcing are discussed.